To solve this system of equations, we can use the method of elimination. We will add the two equations together in a way that eliminates one of the variables.
Adding the two equations, we get:
(6x - 5y) + (3x + 5y) = 27 + 36
Combining like terms, we have:
9x = 63
Dividing both sides of the equation by 9, we find:
x = 7
Now, substitute the value of x into one of the original equations. Let's use the first equation:
6x - 5y = 27
6(7) - 5y = 27
42 - 5y = 27
Subtracting 42 from both sides:
-5y = -15
Dividing both sides by -5, we have:
y = 3
Therefore, the solution to the system of equations is x = 7 and y = 3.
Solving with Elimination Practice
Complete this assessment to review what you've learned. It will not count toward your grade.
1 of 51 of 5 Items
Question
Solve the system of equations.
6x–5y=27
3x+5y=36
(1 point)
2 answers
1. ( 7, 3)
2. ( -4, 2)
3. ( -1, -6)
4. ( 5, 3)
5. ( -1, 4)
2. ( -4, 2)
3. ( -1, -6)
4. ( 5, 3)
5. ( -1, 4)